2004
DOI: 10.1002/j.1551-8833.2004.tb10724.x
|View full text |Cite
|
Sign up to set email alerts
|

role of chlorine and chloramine in corrosion of lead‐bearing plumbing materials

Abstract: A switch from free chlorine to chloramine disinfectant triggered problems with excessive lead in Washington, D.C., drinking water. High levels of lead originated in the service lines, but excessive lead was also derived from solder or brass plumbing materials. In many cases, the highest lead concentrations emerged from the tap after about 1 min of flushing—a troublesome outcome, given that routine public notification recommended that consumers flush for about a minute to minimize lead exposure. Bench‐scale tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
219
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 209 publications
(227 citation statements)
references
References 21 publications
5
219
2
Order By: Relevance
“…The Pb−OH distances in Pb(OH) 2 The thermodynamics of reactions of Pb(III) species showed that they are susceptible to further oxidation to yield Pb(IV) complexes that can be considered as precursors of PbO 2 . ΔG 0 values corresponding to the oxidation of Pb(OH) 2 (H 2 O) 4 •+ and Pb(OH) 3 (H 2 O) 2 • by OH • radicals are −31.4 and −37.5 kcal/ mol, respectively (reactions 6 and 7, Table 1 4,5,16,17,19 Synthesis of EC and QC Data on Pb(III) Formation. EC data demonstrate that traces of PbO 2 nanoparticles deposited on the electrode after the first CV cycle initiate and catalyze the EC generation of OH • radicals, which by reacting preferentially with Pb(II) hydroxo complexes produce Pb(III) intermediates associated with Peak 1.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Pb−OH distances in Pb(OH) 2 The thermodynamics of reactions of Pb(III) species showed that they are susceptible to further oxidation to yield Pb(IV) complexes that can be considered as precursors of PbO 2 . ΔG 0 values corresponding to the oxidation of Pb(OH) 2 (H 2 O) 4 •+ and Pb(OH) 3 (H 2 O) 2 • by OH • radicals are −31.4 and −37.5 kcal/ mol, respectively (reactions 6 and 7, Table 1 4,5,16,17,19 Synthesis of EC and QC Data on Pb(III) Formation. EC data demonstrate that traces of PbO 2 nanoparticles deposited on the electrode after the first CV cycle initiate and catalyze the EC generation of OH • radicals, which by reacting preferentially with Pb(II) hydroxo complexes produce Pb(III) intermediates associated with Peak 1.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…1−3 Both scrutinyite α-PbO 2 and plattnerite β-PbO 2 form via the oxidation by chlorine of Pb(II) solids including hydrocerussite Pb 3 (CO 3 ) 2 (OH) 2 , cerussite PbCO 3 , and massicot PbO 1,4−6 or via the oxidation of Pb(II) solutes. 6 Because PbO 2 has a very low solubility, its presence is deemed to be beneficial for lead release control.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Lead can react with free chlorine in water to produce a red-brown colored solid. It can also leach from brass piping when exposed to chloramines, other commonly used water disinfectants (15). Copper, on the other hand, has antibacterial and antiviral properties (16), but copper piping is not widely spread in Bulgaria.…”
Section: Discussionmentioning
confidence: 99%
“…Discovery of increased lead residual in WASA drinking water occurred in conjunction with the switch from chlorine to chloramines, as the primary disinfectant, in 2001 [3]. After exceeding the lead MCL from 2002 through 2004, WASA conducted full monitoring for lead and copper at customers' taps yearly [4].…”
Section: Introductionmentioning
confidence: 99%